Standing with Sol: The Spirit and Intent of Action Anthropology - Smith, Joshua J. (Anthropologica, 2015)
This paper reflects on Finding a Place to Stand by Michael Asch (2001) in drawing out the political philosophy of Sol Tax’s action anthropology with emphasis on Asch’s "self-relational other," as a means to understand how Canadian anthropologists might eschew the distant position of neutrality and thus, "find a place to stand" within the ongoing struggle for self-determination between Indigenous peoples and Canada. I argue that Tax’s action anthropology is a viable foundation for a relevant anthropology, if not an urgent one, in fostering just relations in Canadian anthropology today. This, in turn, acutely shows how action anthropology is philosophically, politically and historically divergent from other engaged methodologies, such as applied and collaborative anthropologies.